OP12 Similar Svr Rates In Il28b Cc, Ct Or Tt prior relapser, partial- or null-responder patients treated with telaprevir/peginterferon/ribavirin: retrospective analysis of the Realize Study. (6th September 2011) - Foster, G R; Pol, S; Aerssens, J; Zeuzem, S; Andreone, P; Lawitz, E J; Roberts, S; Younossi, Z; Focaccia, R; Horban, A; Pockros, P J; Van Heeswijk, R; et al.
Abstract : Introduction: IL28B polymorphisms are linked to differences in SVR rates in HCV treatment-naÔve patients treated with pegylated interferon (P) and ribavirin (R). REALIZE is a Phase 3 study that compared the efficacy, safety and tolerability of telaprevir (T), with or without a Lead-in (LI), in combination with PR against PR alone in prior treatment-failure patients including relapsers, partial responders and null responders (NR). Both T/PR arms were superior to control in all three patient categories. The relationship between IL28B genotype and SVR was investigated retrospectively. Method: 527/662 (80%) patients enrolled in REALIZE consented to genetic testing. This represented 72%, 76% and 98% of the total relapsers, partial responders, and NR, respectively. Genotype rs12979860 was determined using a TaqMan allelic discrimination assay validated against Sanger sequencing on 50 independent samples. This was a retrospective study based on patients who consented to genetic testing prior to the discovery of IL28B, thus, sample size was not based on formal statistical considerations. Results: Overall, 94% were Caucasian and 4% were Black. 18% of patients were IL28B CC, 61% CT and 21% TT. By prior response category, the highest proportion of IL28B TT patients was among prior NR (28%) while the highest frequency of CC patients occurred among prior relapsers (27%). The observed IL28B genotype frequencies indicate that the population was not in Hardy–Weinberg equilibrium (χ 2 =28, p<0.0001). IL28B genotypes were well balanced across all arms with exception of a higher frequency of TTs in the placebo arm. Since no differences were observed between the two T arms, a pooled analysis is presented. Conclusion: Differences in SVR rates among IL28B CC, CT and TT patients were only evident when the three patient subpopulations were pooled, however, SVR among CT and TT patients were still high. In this retrospective analysis, IL28B genotype did not contribute to outcome prediction in prior treatment-experienced patients treated with a telaprevir-based regimen and thus, may be of limited utility in this setting.